On the Dynamic Properties of Asymmetric Models of Real GNP - Brunner, Allan D. (The Review of Economics and Statistics, 1997)
There is now a substantial body of evidence that suggests business cycles are asymmetric. However, the evidence has been accumulated using a wide array of statistical techniques and, consequently, is based on various definitions of asymmetry. This paper examines several parametric models that have been used to study asymmetries in real GNP. Although these models capture asymmetries in very different ways, their dynamic properties are remarkably similar.